Serum Glucose Level and Hemoglobin Concentration in Third Trimester of Pregnancy - Sufrin, Sumaira; Nessa, Akhtarun; Islam, Md Tazul (Journal of Bangladesh Society of Physiologist, 2016)
Background : Pregnancy is a state of physiological adaptations to accommodate the needs of the developing fetus. Elevated blood glucose during pregnancy could lead to gestational diabetes and anemia could cause intercurrent infection. Objective: To assess the serum glucose level & hemoglobin concentration in third trimester of pregnancy in order to find out the risk of gestational diabetes and physiological anemia. Method: This cross-sectional study was carried out in the Department of Physiology Mymensingh Medical College, Mymensingh, between the period of July, 2013 to June,2014. One hundred pregnant women in their third trimester of pregnancy aged 18-35years were enrolled in study group and age matched 100 healthy non-pregnant women were control group. Random serum glucose was estimated by GOD-PAP method and hemoglobin concentration was measured by cyanmethemoglobin (CMG) method. Data were analyzed by students un paired t test and chi square test. Result: Mean serum glucose level (6.76±1.72 mmol/L) was significantly higher and hemoglobin concentration (8.21±1.23 g/dl) was significantly lower in pregnant women than non-pregnant women. Increased frequency of high glucose (38%) and low H b(88%) was found in pregnant women in third trimester. Conclusion: This study concludes altered glucose metabolism may lead to gestational diabetes as well as physiological anemia may be exaggerated in third trimester of pregnancy Bangladesh Soc Physiol. 2015, December; 10(2): 67-70